Mixed stabilized finite element methods in nonlinear solid mechanics Part I: Formulation - CERVERA, M; CHIUMENTI, M; CODINA, R (Computer methods in applied mechanics and engineering, 2010)
This paper exploits the concept of stabilized finite element methods to formulate stable mixed stress/displacement and strain/displacement finite elements for the solution of nonlinear solid mechanics problems. The different assumptions and approximations used to derive the methods are exposed. The proposed procedure is very general, applicable to 2D and 3D problems. Implementation and computational aspects are also discussed, showing that a robust application of the proposed formulation is feasible. Numerical examples show that the results obtained compare favorably with those obtained with the corresponding irreducible formulation.